Deviant Behavior as Among Major Factors Contributing to Poor Performance in Certificate Secondary Education Examination: A Case of Micheweni Secondary School in Zanzibar, Tanzania - Ahmed, Othman Mohammed (2018)
Since independence of 1964, Tanzania had given priority to her citizens in ensuring that better and quality education is easily accessible to all. Both the government of United Republic of Tanzania and Revolutionary Government of Zanzibar has had been adopted and implemented variety of educational polices, approaches and strategies and regulations with the aim of bringing not only enhanced secondary education but also sustainable one and which can practically be implemented by students hence developing themselves in conjunction with bringing sustainable development to their nation. It is in this line therefore, this paper aiming to enlighten how deviant behavior contributing to poor performance for Zanzibar secondary school students. Using descriptive approach, school and home based factors determined to cause student deviant behaviors which influence students’ performance in national examination certificate of secondary education in Zanzibar. The study was conducted in northern part of Zanzibar, Tanzania since is among leading regions in terms of poor performance from secondary education examination results (Mwesiga, 2000). The study employed both qualitative and quantitative approaches. Qualitative approach was used in the form of interviews while quantitative approach was used in the form of questionnaires. Findings revealed that home and school environments both contribute in causes of deviant behavior to secondary school students which sooner influence their performance. Due to the perseverance of carving down of disciplines in secondary schools, deviant behavior is always available. Late coming, not doing school assignments in time, violation of dressing code, ruddiness, lying, fighting with fellow students, leaving school before time and skipping classes are most frequently identified deviant behavior in secondary schools however community takes initiatives in monitoring them so as to reduce the extent of its impact towards students’ performance. Based on the findings, this study recommends stakeholders to increase initiatives in maintaining discipline among students and encourage them to like reading or learning and not engaging other activities which interns lead them not only having deviant behavior but also experience poor performance. Also issue of deviant behavior with its impacts should well be addressed not only in education policy but also in other related policy documents and other researches since still there is need of exposing much of unknown aspects of deviant behavior with respect to students’ performance. Key Words: Education, Deviant behavior, Certificate Secondary Education Examination, Student, Poor Performance, Micheweni Secondary School, Zanzibar, Tanzani